1999
DOI: 10.1149/1.1391977
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature on the Impedance of Poly‐o‐toluidine in 3.7 M  H 2 SO 4

Abstract: Many aspects of the conduction mechanism and the electrochemical switching of arylamine-derived polymers are still under discussion. 1,2 Although a variety of techniques has been applied to the study of these problems, the effect of temperature has received little attention. [3][4][5][6][7][8] On the other hand, electrochemical impedance spectroscopy (EIS) has proved to be a powerful technique for studing the electrochemical behavior of this kind of polymers. Several impedance studies of poly(aniline) (PANI) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The base electrodes were gold wires 2 cm long and of 0.5 mm radius. Pani films were obtained by electro polymerization on Au electrodes [15,16]. The electrosynthesis were carried out by cycling the potential at 0.10 V s −1 between − 0.20 V vs. SCE and a positive potential limit set at the beginning of the monomer oxidation (around 0.70-0.80 V).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The base electrodes were gold wires 2 cm long and of 0.5 mm radius. Pani films were obtained by electro polymerization on Au electrodes [15,16]. The electrosynthesis were carried out by cycling the potential at 0.10 V s −1 between − 0.20 V vs. SCE and a positive potential limit set at the beginning of the monomer oxidation (around 0.70-0.80 V).…”
Section: Methodsmentioning
confidence: 99%
“…To improve the adherence and homogeneity of the film, after a few cycles, the positive potential limit was slightly decreased. A conventional three electrode glass cell was employed [15,16]. After the synthesis, the films were washed with pure water and cycled in 3.7 M H 2 SO 4 solution, until the stationary voltammetric profile is achieved.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in the whole field of conducting polymers, only a few works on changing this variable have been reported. 13,[27][28][29][30][31][32] To our knowledge, no studies of the temperature dependence of the relaxation phenomena have been reported. Therefore, we think that more insight on the relaxation effect can be obtained from the study of its the temperature dependence.…”
mentioning
confidence: 99%
“…However, the obtained high resistances of R 1 and R 2 are characteristic of a nonconductive polymer layer. In the literature, it usually includes resistance of polymer layer, and resistance of pores within the polymer that are filled with electrolyte 23, 24. Because PANI1‐OPDA5 shows higher resistance values compared to PANI1, the size of pores and the amount of the solution within the pores should therefore be smaller in the case of PANI1‐OPDA5 (i.e., the layer is more compact).…”
Section: Resultsmentioning
confidence: 99%